microRNAs as Developmental Regulators - Ivey, Kathryn N. (Cold Spring Harb Perspect Biol, 2015)
The field of miRNA biology is relatively young, but its impact on our understanding of the regulation of a wide array of cell functions is far-reaching. The importance of miRNAs in development has become nearly ubiquitous, with miRNAs contributing to development of most cells and organs. Although miRNAs are clearly interwoven into known regulatory networks that control cell development, the specific modalities by which they intersect are often quite distinct and cleverly achieved. The frequently emerging theme of feed-back and feed-forward loops to either counterbalance or reinforce the gene programs that they influence is a common thread. Many of these examples of miRNAs as developmental regulators are presently found in organs with different miRNAs and targets, whereas novel, unexpected themes emerge in the context of mouse development as we learn more about this rapidly developing area of biology.